2013
DOI: 10.1038/bjc.2013.666
|View full text |Cite
|
Sign up to set email alerts
|

The impact of body mass index on complication and survival in resected oesophageal cancer: a clinical-based cohort and meta-analysis

Abstract: Background:Body mass index (BMI) has been associated with the risk of oesophageal cancer. But the influence of BMI on postoperative complication and prognosis has always been controversial.Methods:In total, 2031 consecutive patients who underwent oesophagectomy between 1998 and 2008 were classified according to Asian-specific BMI (kg m−2) cutoff values. The impact of BMI on overall survival (OS) was estimated using the Kaplan–Meier method and Cox proportional hazard models. We performed a meta-analysis to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
127
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(143 citation statements)
references
References 35 publications
15
127
0
1
Order By: Relevance
“…Multivariate analyses carried out in various studies have shown that preoperative BMI is an independent prognostic factor for reduced survival, and that it is strongly associated with postoperative complications in esophageal cancer 59. Wang et al 60.…”
Section: Resultsmentioning
confidence: 99%
“…Multivariate analyses carried out in various studies have shown that preoperative BMI is an independent prognostic factor for reduced survival, and that it is strongly associated with postoperative complications in esophageal cancer 59. Wang et al 60.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified several independent prognostic factors that are associated with postoperative complications and survival in patients who underwent two- to three-field LN dissection for locally advanced esophageal cancer [14,15,16,17,18]. However, each of these factors was identified from data on retrospective cohorts, and no prognostic index has been proposed on the basis of clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…For squamous cell carcinomas at other sites, this role seems to be different. In esophageal cancer BMI is an independent favorable predictor of survival [18]. Head and neck squamous cell carcinoma studies also showed that high BMI was associated with lower risk of mortality [19] or at least for smokers [20].…”
Section: Discussionmentioning
confidence: 99%